Building business value through talent : the CEO and CHRO partnership guide - McGuire, Thomas; Brenner, Linda (Emerald Publishing Limited, 2021)
Building Business Value through Talent uniquely describes how a CEO and CHRO can accelerate business growth by working together to design and operationalize value-driven talent strategies. CEOs focus on decisions that will drive the business strategy forward while HR leaders routinely try to satisfy the needs of the largest number of employees. Often, the two align superficially or in administrative ways - and to put out the occasional flash fire. This book changes that dynamic by unlocking the investment potential of HR and empowering an unprecedented, tangible and measurable partnership between CEOs and CHROs. Framed as a product guide, the "product" is visualized as the HR Operating Model necessary to succeed in our modern economy: a business-based talent planning and investment strategy to sustain talent solutions and intellectual capital growth. This product guide provides the tools and insights that business leaders are seeking in order to win the ever more challenging battles in their war for talent. Learning and adopting these winning practices will provide a visible testament to the effective leadership of any CEO and CHRO team.